STUDENT WORKBOOK USE: DOES IT STILL MATTER TO THE EFFECTIVENESS OF STUDENTS’ LEARNING? - Alvi Raihan Utami; Dyah Aminatun; Nina Fatriana (Journal of English Language Teaching and Learning, 2020)
One effort that teachers can do to improve their learning process is by developing learning resources for themselves and their students. Teachers can use student workbook (LKS) to be used as a source of learning for students. A student workbook that contains material summaries can help students more effectively understand the materials. Student workbook containing a variety of practice questions is believed to affect the effectiveness of student’s learning. This research aims to analyze the effects of using student workbook (LKS) towards the effectiveness of students’ learning. This research was conducted to see students' perceptions of the role of using student workbook (LKS) towards the effectiveness of student learning. To collect data, this study used a questionnaire distributed to 24 students using a survey administration application, consisting of six questions related to the students' perceptions of the role of using student workbook (LKS) towards student’s learning process. After all, participants had completed the questionnaire, the data were then categorized based on relevant findings. The findings reveal that the use of student workbook gives beneficial impact on students’ learning since it can be one of the sources of learning besides the teacher’s explanation. It also makes students easier in understanding the materials with simple content and various practices. In the end, this research hopefully can be useful as a reference or guide for future researchers who want to conduct similar research on the use of student workbook (LKS) as one of the resources in the teaching process.